2018
DOI: 10.1002/2017jc013562
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variability of Eddy Kinetic Energy in the Subtropical Southeast Indian Ocean Associated With the El Niño‐Southern Oscillation

Abstract: Interannual variability of eddy kinetic energy (EKE) in the subtropical southeast Indian Ocean (SEIO) is investigated using satellite observations in three regions in the 20°S–35°S latitude band: R1 (108°E–115°E), R2 (100°E–108°E), and R3 (60°E–100°E). The El Niño‐Southern Oscillation (ENSO) plays an important role in modulating the interannual variability of EKE in the SEIO. EKE in the three regions shows negative correlations with the Nino3.4, lagging Nino3.4 by 2, 14, and 22 months, respectively. In R1, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 48 publications
1
32
1
Order By: Relevance
“…We also examined the lagged correlations of the climate mode indices with mesoscale EKE averaged in the eastern SSIO and west central SSIO (Figure ), in order to consider the aggregate impact of the climate modes in these distinct regions of mesoscale eddy variability. The time series of eastern SSIO EKE lp and EKE meso is closely aligned with the Niño3.4 index (Figure a), and the negative Niño3.4‐EKE meso correlation is very likelyless than −0.5 at lags of 3–6 months (Figure b), indicating a very robust influence from ENSO as Zheng et al () found. However, despite the localized negative correlation of SAM in part of the E SSIO region, there is no significantly robust correlation between SAM and EKE meso in the E SSIO region overall (Figures c and d), implying the dominance of the ENSO influence in this region.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…We also examined the lagged correlations of the climate mode indices with mesoscale EKE averaged in the eastern SSIO and west central SSIO (Figure ), in order to consider the aggregate impact of the climate modes in these distinct regions of mesoscale eddy variability. The time series of eastern SSIO EKE lp and EKE meso is closely aligned with the Niño3.4 index (Figure a), and the negative Niño3.4‐EKE meso correlation is very likelyless than −0.5 at lags of 3–6 months (Figure b), indicating a very robust influence from ENSO as Zheng et al () found. However, despite the localized negative correlation of SAM in part of the E SSIO region, there is no significantly robust correlation between SAM and EKE meso in the E SSIO region overall (Figures c and d), implying the dominance of the ENSO influence in this region.…”
Section: Resultssupporting
confidence: 66%
“…The relationship of the northwestern tropical Pacific SLA and mesoscale EKE in the eastern SSIO region suggests that ENSO or decadal variability in the tropical Pacific can induce variations of eddy activity in the SSIO, a hypothesis supported by the influence of ENSO on the strength of the Leeuwin Current (Feng et al, ) where much of the eddy generation occurs. Jia, Wu, Lan, and Qiu () discussed a significant negative correlation between spatially averaged EKE meso in the southeast Indian Ocean and the SAM, while Zheng et al () explored the influence of ENSO on eddy activity in the SSIO. However, the westward extent of the influence of climate modes on EKE meso has not been clearly mapped, and the climate influence on SSIO mesoscale eddy activity has not been assessed on decadal to multidecadal time scales.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations